2018
DOI: 10.31294/w.v10i1.2710
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grammar and Vocabulary Mastery on Students’ Reading Comprehension

Abstract: The objective of the research is to know the effects of grammar and vocabulary mastery on students' reading comprehension. This research is a survey at private universities in Bekasi. The total sample of the research is 80 students. The data collection technique of grammar mastery, vocabulary mastery, and reading comprehension is by conducting three sets of multiple choice tests consisting of 30 questions for each test. The data analysis technique of the research is multiple linear regression analysis. Before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In language learning, vocabulary is the tool of thought, self-expression, translation and communication. Hornby in (Yuliawati, 2018) defined vocabulary as a list of words with their meanings that plays an important role in understanding the language holistically. In any language teaching, vocabulary plays a tremendously important role.…”
Section: Introductionmentioning
confidence: 99%
“…In language learning, vocabulary is the tool of thought, self-expression, translation and communication. Hornby in (Yuliawati, 2018) defined vocabulary as a list of words with their meanings that plays an important role in understanding the language holistically. In any language teaching, vocabulary plays a tremendously important role.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if the students have good grammar and vocabulary mastery, they can comprehend a text correctly. This statement is supported by Yuliawati (2018) who conducted to investigate the effect of grammar and vocabulary on reading comprehension at private university in Bekasi. The finding showed that there is significant effect of vocabulary mastery on students reading comprehension.…”
Section: The Correlation Between Students' Vocabulary Mastery (X1) An...mentioning
confidence: 72%
“…In other words, vocabulary mastery is needed to help students use each word appropriately in producing good writing. Vocabulary mastery refers to someone's ability in using words and their meaning properly in language (Yuliawati, 2018). Consequently, students should explore and enlarge their vocabularies to enhance their writing quality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to improve their writing skill, students should also have good grammar mastery. Grammar mastery means the ability to understand the theory of sentence such as functions, units, or forms and the ability to produce standard forms in accordance with the rules and regulations (Yuliawati, 2018). Unfortunately, several existing researches on grammar teaching have a limitation, which is there is no clear conceptualization of a theoretical rationale for why grammar might support writing development (Jones, Myhill, & Bailey, 2013).…”
Section: Introductionmentioning
confidence: 99%